“Solely an Act of Prayer”—and Power? Ordination in the Swiss Reformed Church and the Question Who Ordains Who, or Not - Stephany, André M. (Studia liturgica, 2025)
This article discusses how the Swiss Reformed Church (SRC) is very aware of power-structures and keen to enact its democratic understanding of church in the ritual of ordination. The same Church, however, is hesitant to enter the debate about ordained ministry and to consider the ordination of those from ministries other than the stipendiary ministry of the Word and Sacrament. Following debates about the ordination of deacons and catechists, the question of which ministries should be ordained has reclaimed significance: first, because there is a growing number of lay readers who partake in the ministry of the Word and Sacrament and play an increasingly important role in the SRC and, second, from an ecumenical perspective, because the SRC is a member of the Community of Protestant Churches in Europe (CPCE) that sees ordination as the condition for the public proclamation of the Word and the administration of the sacraments. This article argues that the effort to enact ordination liturgically as a democratic and non-hierarchical act stands in marked contrast to the protectionist treatment of the one ordained stipendiary office of the Word and Sacrament. Does power play a role despite the enactment of a power-free ordination liturgy?